Gamson–Modigliani Framing Analysis on Cin(T)a and 3 Hati 2 Dunia 1 Cinta - Deavvy M.R.Y Johassan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The journey of the national film industry has a long history. Gradually, the film industry has become a mere commercial industry dominated by horror and comedy films. This has resulted in the formation of stereotypes that all national films have the same content and do not vary. The films